Pseudophotographs in Children’s Literature: A New Object for Photoliterature Studies - Shamshul Ariffin, Alya; Beauvais, Clémentine (Mémoires du livre / Studies in Book Culture, 2024)
This article proposes to theorize the study of pseudophotographs as a subtype of photoliterature studies. Pseudophotographs are any illustrations understood within the context of a picturebook or graphic novel to be representations of photographs. This article attempts to define this undertheorized graphic object, to discuss its various functions, and to analyse what pseudophotographs can tell us about how real photographs and photography are considered in children’s literature. Because pseudophotographs appropriate some of the conventions of photography and yet are unlike real photographs in many ways, they are, we argue, a significant place for implicit discourse about the art and practice of photography and about affective encounters with photographs.